Duração do sono e sonolência diurna em adolescentes do ensino médio da cidade de Fortaleza - Alves, Felipe Rocha (2018)
The advent of antiretroviral therapy has reduced the incidence of adverse events and early mortality in HIV-infected person. However, it’s observed the health of this population isn’t completely reestablished. In this population has been common inflammatory comorbidities cases. The possible cause is the GALT tissue due, it causes a bacterial translocation and takes the organism exposed to inflammatory microbial products. The study’s objective is to determine the levels of inflammatory markers in patients with HIV infection in ambulatory follow-up and to observe possible influence of social, behavioral, clinical, immunological and virological variables. It is an observational, prospective, transversal and analytical study carried out in the ambulatory service specialized in HIV/AIDS at integrated medical attention nucleus (SAE-NAMI) between May 2016 to May 2017. They’ve participated in the study 137 patients with an median age of 36.5 years. The study has observed an increase in inflammatory markers of HIV positive when has compared with HIV negative individuals, but only the IL-6 showed a significant difference (IL-6: p = < 0.0001). No significant difference has observed when we compared the values of inflammatory markers with social, behavioral, clinical and virological data. In this way, abnormal levels of inflammation and activation in HIV positive occur indirectly to the HIV virus, where inflammation occurres through other pathways. The bacterial translocation can be resulting in increased levels of inflammatory markers. This way, new studies are needed to clarify these pathogenic ways of increasing inflammation. The bacterial translocation is a probably way about inflammation increased in HIV positive patients.